The Halliburton Agenda : The Politics of Oil and Money - Briody, Dan (Hoboken, New Jercy John Wiley & Sons INC, 2004)
"In The Halliburton Agenda, Halliburton and its subsidiary, Kellogg Brown & Root, form the foundation of an intriguing story of cronyism and conflict of interest that has only increased in momentum over the last decade.
Include Notes, Bibliography and Index
Keywords: Halliburton Company -- Brown & Root, Inc -- United States